Using the Van Hiele Theory to Explain Pre-Service Teachers' Understanding of Similarity in Euclidean Geometry - Mduduzi Mbatha; Sarah Bansilal (MDPI AG, 2023)
Helping learners to develop a solid grasp of geometric concepts poses a challenge for teachers. Therefore, it is important that teachers have a sound understanding of the geometry they teach. The aim of this qualitative study was to explore pre-service teachers' (PST's) understanding of the concept of similarity in Euclidean geometry and to use van Hiele's theory to explain misconceptions evidenced by the PSTs. Data in this study were collected from 34 first-year PSTs studying for a Bachelor of Education degree in high school mathematics. The authors analysed the written responses to a 13-item worksheet and also conducted interviews with seven of the participants. The analysis of the data was guided by van Hiele's theory which was used to identify misconceptions amongst PST's who had not yet developed the appropriate reasoning skills linked to particular van Hiele levels of geometric thought. It was found that these students used reasoning that is characteristic of the elementary levels to make judgments. Many PST's faced challenges with similarity notation and the process of proving the similarity between two figures. This study recommends that PST's should be given more opportunities to connect visual and analytic representations of similarity.